Mass movement study along BR-101 highway in Campos dos Goytacazes,RJ - José Luiz Ernandes Dias Filho; Priscila Alves Marques Fernandes; Maria da Glória Alves (Vértices, 2013)
Mass movements are continuous natural phenomena and external dynamics, like weathering and erosion processes. The study presents an analysis of mass movements along the BR101 highway in Campos dos Goytacazes, Rio de Janeiro. For this purpose, a field survey was carried out, in which the causes of 13 occurrences of mass movements were identified and analyzed. The occurrences were related to the deficiency and maintenance of drainage ways, associated with weathering activities, in a region of average susceptibility to erosion. The mass movements presented in the study offer low risk to the population.